Ascorbic acid-assisted defect healing and stack ordering of graphene films towards high power thermal dispersion. (September 2021) - Pan, Zuo; Wu, Yanhong; Yuan, Hong; Tang, Runli; Ji, Lei; Zhou, Bucun; Ye, Chuanren; Zhang, Dawei; Qu, Yan; Ji, Hengxing; Zhu, Yanwu
Abstract: The thermal dispersion power depends on thermal conductivity and thickness of the thermal dispersion material that is a critical component of modern electronic devices due to the demands of high operating power in a miniaturized space. Films made of assembled graphene flakes have been becoming an emerging thermal dispersion material owing to their high thermal conductivity and tunable thickness up to millimeters, which outperform that of artificial graphite films made from polyimide. But the thermal conductivity typically decreases with the increase of film thickness. In our work, by pre-reducing the graphene oxide with Vitamin C and sequentially annealing the stacking films at 2950 °C, a 80 μm-thick graphene film (GF) with an in-plane thermal conductivity of above 1600 W/(m·K) is achieved. Detailed characterizations indicate that, the addition of Vitamin C is beneficial to the assembly ordering of graphene oxide platelets and the defect healing during the thermal annealing, which both contribute to the excellent thermal conductivity of the films. Our work provides an industrially scalable strategy towards high performance heat dissipation films for future electronic devices. Graphical abstract: Image 1